Community transformation through community infrastructure planning: A case study of Song District, Sarawak - Mark Anak Edward Tuah,; Peter Aning Tedong,; Melasutra Md. Dali, (Penerbit Universiti Kebangsaan Malaysia, 2023)
The development of community infrastructure is fundamental to the socio-economic growth of a region and its community. Nevertheless, the development of rural community infrastructure still remains a challenge in some rural areas which affects the standard of living in the communities. In Malaysia, community infrastructure planning remains a key component of Malaysia’s rural development policies and strategies that needs to be amplified in ensuring the sustainable development of rural areas. This paper examines the role of community infrastructure planning in transforming rural communities’ quality of life which includes the impacts of community infrastructure planning to community’s livelihood transformation and challenges that comes with it. This study adopts the qualitative approach involving semi-structured in-depth interviews with relevant government agencies involved in the rural community infrastructure planning process. Based on a study carried out in Song District, Sarawak, the findings finds that while the respondents agreed that development of community infrastructure in the district have created transformational effects to the communities’ livelihoods, there were various challenges to the delivery of community infrastructure projects to certain areas within the district in addition to satisfying the needs to the community. The discussion suggests that in terms of governance, integration of institutional roles of stakeholders, involving government agencies and community needs to be emphasize in the rural community infrastructure planning process to deal with the many challenges in order to fulfill the rural communities’ needs.